Metacognitive experiences, skills and self-efficacy beliefs in writing: A case study of a pupil with Asperger syndrome - Stamouli, Areti (2012)
The current research constitutes a multi-method case study with a focus on the metacognitive regulatory skills, the emotional experiences and the selfefficacy beliefs of a student with Asperger syndrome while producing a text. The literature review indicates that children with Asperger syndrome are unable to monitor and control the writing process and the emotional condition of self within it, amongst other writing difficulties they face. This intertwines with the development of inaccurate self-efficacy beliefs about writing a text. The current study employs highly structured as well as open, more qualitative research tools to explore those issues whilst a theory-based categorization of data is applied. The findings reveal that both cognitive and emotional self-monitoring occur in the mind of the focus child with Asperger syndrome while this awareness links with more accurate self-efficacy beliefs about writing. However, the great difficulty lies in the student’s incomplete knowledge of control mechanisms to deal with the challenges of writing, a point that highlights the need for an intensive cognitive instruction of text planning and revising skills. The limitations of current research and some suggestions for future research are finally exposed.